Inaccuracy of three-finger pinch method of determining salt content in homemade sugar salt solutions - Wilcox, W.D.; Miller, J.J. (Wilderness & environmental medicine, 1996)
Oral rehydration therapy (ORT) has dramatically reduced the morbidity and mortality associated with acute infectious diarrhea. Commercial oral rehydration salt (ORS) solutions with sodium concentrations of 30–90 mmol/L are ideal for both the prevention and treatment of dehydration. However, logistic issues impede their universal availability and homemade sugar salt (HSS) solutions are widely used in some areas of the world. The least accurate methods of preparing HSS solutions utilize a three-finger pinch of salt. The present study demonstrates the inconsistency and inaccuracy of this method among 15 health workers who participated in an ORT training seminar conducted in a situation that approximated field conditions. Similar studies with different subjects, instructions, and milieu describe results similar to those we obtained. In all studies, including the present one, a substantial number of the solutions prepared by this method had dangerously high or low sodium concentrations. Health providers should consider the use of selected home-available fluids rather than HSS solutions for the prevention of dehydration in children with diarrhea. However, ORS solutions should be used to correct established dehydration.